Relevância de variantes genéticas para eNOS, ELN, COL1A2, ENG e VEGF em aneurisma intracraniano familial - Gregório, Michele Lima (2014)
Environmental and genetic risk factors are involved in the development of intracranial aneurysm (IA).Objectives - evaluate the association of genetic polymorphisms for endothelial nitric oxide synthase (eNOS-G894T), collagen (COL1A2-Ala459Pro), elastin (ELN-A442G), endoglin (ENG-Ins/Del) and vascular endothelial growth factor (VEGF-C936T) in patients wih familial and sporadic IA and in their first-degree relatives; analyze the relationship between polymorphisms, lifestyle, presence of hypertension (HAS) and diabetes mellitus (DM); evaluate the relationship between these polymorphisms considering the morphological features of intracranial aneurysms and ruptured aneurysms in familial and sporadic groups. Methods - We selected 847 individuals, distributed as follows: G1 - 43 patients with familial AI; G2 - 177 first-degree relatives of G1; G3 - 115 patients with sporadic AI; G4 - 276 first-degree relatives of G3; G5 - 106 individuals without IA; G6 - 130 first-degree relatives of G5. The polymorphisms were performed by PCR / RFLP. Level of significance for P <0.05. Results- eNOS-G894T: prevalence of allele T and T/T genotype in patients (G1 and G3) and their families (G2 and G4) compared to the control group (G5) and G5 and G6 (P <0.01). ELN-A442G: prevalence of the genotype A/G in all groups and prevalence of the allele A in G2 versus G6 (P = 0.003). ENG-Ins/Del: the genotype Ins/Ins was highlighted in G1 and G2, G5 versus (P = 0.006) and G6 (P = 0.001), while the genotype Wt/Ins prevailed in G5 versus G1 (P = 0.001). COL1A2-Ala459Pro: prevalence of the genotype C/C in G2 in relation to G6 (P = 0.016). VEGF-C936T: prevalence of the genotype C/C in G6 compared to G4 (P <0.0001). Smoking/alcohol consumption X genotypes: higher frequency of smokers in G3 compared to non-smokers (P = 0.034) with risk genotype (_/C of COL1A2). For ENG-Ins/Del the combination of genotype (Wt/Wt) + no smoking prevailed G5 compared to G1 (P = 0.008). In G1 and G3 the combination of the _/T (VEGF- C936T ) + smoking prevailed in comparison to G5 (P < 0.05). In G5 the combination of the G/G (COL1A2 - Ala459Pro) + non-alcohol drinkers prevailed compared to G3 (P = .0001) and the combination C/C (VEGF - C936T) + non-alcohol drinkers between G5 and G3 (P = 0.001). Hypertension/Diabetes X genotypes: Higher frequency of normotensive and non-diabetic patients with genotype G/G (COL1A2-Ala459Pro) in G5 compared to G3 (P=0.0005 and P = 0.0003, respectively), however the combination _/C + normotensive prevailed in G2 compared to hypertensive (P <0.0001). For VEGF-C936T there were higher frequency of non-diabetic with genotype C/C (P = 0.0007), however, G1 showed higher frequency of genotype _/Ins (ENG-Ins/Del) + diabetic compared G5 (P = 0.020). Genotype combinations: the combination of risk genotypes (_/T + _/G + _/Ins + _/T + _/C) prevailed in G1 and G3 compared to G5 (P = 0.01 and P = 0.032, respectively) and the protective genotypes (_/G + _/A + _/Wt + _/C + _/G) prevailed in G5 in comparison to G1 and G3 (P <0.0001 for both). Morphology and rupture: similar values for the variables: number, location, size, type of neck and genotype in relation to aneurysms with or without rupture. Conclusions - Polymorphisms involved in the arterial development modify the vascular integrity, since they are associated in families with familial or sporadic AI and their families. Rupture is independent of the location and morphology of IA, as well as the polymorphisms evaluated.